Pietra ollare artefacts from Červar Porat (Istria, Croatia): composition and possible origin - Tibljaš, Darko; Balen, Dražen; Šimić-Kanaet, Zrinka Girardi Jurkić, Vesna (2010)
During archaeological excavations performed between 1976 and 1980 at a Roman villa rustica in Červar-Porat located close to the town Poreč (Istria peninsula, Croatia), among other Late Antique period fragments (glass, metal, eramics), fourteen peculiar stone vessel fragments were discovered. They show characteristic tracks of the manufacturing by means of lathe. Vessels made by analogous processes from similar materials have already been found at several localities at Croatian Adriatic coast, but no systematic mineralogical study on this kind of material was performed so far. Two of these vessel fragments were recently investigated in more detail by mineralogical methods. The first one (inv. no. 7912) is greenish-grey in colour (Fig. 1). X-ray powder diffraction revealed that the only constituent of this fragment is a chlorite group mineral. The mineral composition together with visible schistosity indicates that source material was chloriteschist, a low–grade metamorphic rock. Such material is one of different lithologies included by Italian term pietra ollare and German Lavez. The other fragment (inv. no. 7907) is dark greenish-grey on the fresh broken surface and brownish on outer and inner vessel surfaces. Distinctive bronze coloured flakes can be seen in some parts. The fact that XRD pattern of the second fragment was similar to the XRD pattern recorded on the material from the first fragment after heating to 1100ºC indicate that the second vessel was most probably used for cooking, and during that process it was exposed to elevated temperatures. In order to determine possible origin of analysed fragments their mineral and chemical composition was compared with those recorded for samples collected in Valle d’Aosta and Valli di Lanzo (north-western Italy) and literature data for pietra ollare originating from other localities in Italian Alps.
Projekt MZOS
ENG